2020
DOI: 10.1002/mnfr.202000288
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Oligofructose Prevents Antibiotic‐Induced Obesity Risk and Improves Metabolic and Gut Microbiota Profiles in Rat Dams and Offspring

Abstract: ScopeAntibiotics in early life disrupt microbiota and increase obesity risk. Dietary agents such as prebiotics may reduce obesity risk. The authors examine how antibiotics administered with/without prebiotic oligofructose, alter metabolic and microbial outcomes in pregnant rats and their offspring.Methods and ResultsPregnant rats are randomized to: 1) Control, 2) Antibiotic (ABT), 3) Prebiotic (PRE), 4) Antibiotic+Prebiotic (ABT+PRE) during the 3rd week of pregnancy and lactation. Offspring were fed a high fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Inulin was a common prebiotic, and the in vivo studies showed that the intake of inulin oligofructose improved obesity, glycemic dysregulations, and the blood-brain-barrier integrity, with decreasing the Firmicutes to Bacteroidetes ratio while increasing Bifidobacterium abundance [ 58 , 59 ]. Additionally, the pregnant rats which received oligofructose had a lower obesity risk in their offspring, with higher abundances of Bifidobacterium and Collinsella [ 60 ]. Besides, fucoidan polysaccharides could improve gut microbial diversity with increasing the abundance of Bacteroidetes and Proteobacteria , enhancing the bile salt hydrolase activity of Lactobacillus casei DM8121, as well as upregulating the expression of hepatic cholesterol 7-α hydroxylase, while the abundances of Actinobacteria and Firmicutes were decreased [ 61 , 62 ].…”
Section: Mechanisms Of Probiotics Prebiotics Synbiotics and Postbiotics On Metabolic Diseases By Targeting Gut Microbiotamentioning
confidence: 99%
“…Inulin was a common prebiotic, and the in vivo studies showed that the intake of inulin oligofructose improved obesity, glycemic dysregulations, and the blood-brain-barrier integrity, with decreasing the Firmicutes to Bacteroidetes ratio while increasing Bifidobacterium abundance [ 58 , 59 ]. Additionally, the pregnant rats which received oligofructose had a lower obesity risk in their offspring, with higher abundances of Bifidobacterium and Collinsella [ 60 ]. Besides, fucoidan polysaccharides could improve gut microbial diversity with increasing the abundance of Bacteroidetes and Proteobacteria , enhancing the bile salt hydrolase activity of Lactobacillus casei DM8121, as well as upregulating the expression of hepatic cholesterol 7-α hydroxylase, while the abundances of Actinobacteria and Firmicutes were decreased [ 61 , 62 ].…”
Section: Mechanisms Of Probiotics Prebiotics Synbiotics and Postbiotics On Metabolic Diseases By Targeting Gut Microbiotamentioning
confidence: 99%
“…There is accumulating evidence that treatment with inulin and oligosaccharides increases the abundances of Collinsella and Bifidobacterium in the guts of rats [21]. In this study, treatment with AL and AP increased the levels of Collinsella, showing that AL and AP are similar to prebiotic oligosaccharides concerning their effect on Collinsella.…”
Section: Collinsellamentioning
confidence: 49%
“…Body mass, fat mass, percent body fat, and bone mineral content plus lean mass were determined for each animal at the endpoint of diets using dual energy X-ray absorptiometry (DXA) and analyzed with software for small animal analysis (Hologic QDR 4500; Hologic, Bedford, MA). These procedures and data from these same animals have been reported previously (Boldt et al 2020a(Boldt et al , 2020bCollins et al 2015Collins et al , 2016aCollins et al , 2016bCollins et al 2016c;Klancic et al 2020Klancic et al , 2021Rios et al 2020), but data are re-reported to reflect the specific animals used in assessments of single fibres.…”
Section: Body Compositionmentioning
confidence: 75%